Factors associated with antimicrobial-resistant Escherichia coli in zoo animals - Ishihara, K.; Hosokawa, Y.; Makita, K.; Noda, J.; Ueno, H.; Muramatsu, Y.; Mukai, T.; Yamamoto, H.; Ito, M.; Tamura, Y. (Elsevier, 2012)
Factors associated with the carriage of antimicrobial-resistant Escherichia coli isolates were analysed among zoo animals. An association was observed between selection of amoxicillin as the first-line therapy and a significantly higher percentage of resistance to ampicillin (54.5%) from 11 animals treated with antimicrobials, compared with isolates from 32 untreated animals (9.4%). In addition, the percentage resistance to kanamycin (36.4%), gentamicin (27.3%), trimethoprim (27.3%) and tetracycline (63.6%) from 11 treated animals was significantly higher than those from 32 untreated animals (3.1%, 3.1%, 3.1% and 25%, respectively), although these antimicrobials were rarely used. All kanamycin-, gentamicin- and trimethoprim-resistant isolates and more than half of the tetracycline-resistant isolates from treated animals were also resistant to ampicillin. Co-resistance to other antimicrobials with ampicillin was suggested to contribute to an increasing of resistance towards antimicrobials that were rarely administered. The present investigation revealed an association of antimicrobial treatment with the spread of antimicrobial-resistant bacteria among zoo animals.